Levofloxacin: Is It Still Suitable as an Empirically Used Antibiotic During the Perioperative Period of Flexible Ureteroscopic Lithotripsy? A Single-center Experience with 754 Patients - Ao, Ping; Shu, Ling; Zhang, Zhenxing; Zhuo, Dong; Wei, Zhongqin (Urology Journal, 2020)
Purpose: To determine the empirical usage of antibiotics and analyze the pathogen spectrum during the perioperative period of flexible ureteroscopic lithotripsy (FURSL) with a focus on levofloxacin. Materials and Methods: This retrospective analysis included 754 patients who underwent FURSL successfully in our hospital from January 2015 to July 2019. All patients were indicated urine cultures and prescribed antibiotics during the perioperative period. Patients with negative preoperative urine cultures were divided into levofloxacin (LVXG) and non-levofloxacin groups (NLVXG) based on the empirical use of antibiotics. Operative time, the length of postoperative hospital stays and total hospital stays, total hospitalization costs, postoperative fever rate and removal rate of stones were compared. Patients with positive urine cultures were analyzed for pathogen distribution and antibiotic resistance. Results: In the empirical use of antibiotics among 541 cases with negative urine cultures, the prescription rate of levofloxacin was 68.95%. Compared to that in NLVXG, LVXG had a lower cost of antibiotics but higher postoperative fever rate and longer hospital stay. There were no significant differences in operative time, the total hospitalization costs and the removal rate of stones between the two groups. The top two common pathogens were Escherichia coli (36.11%) and Enterococcus faecalis (24.07%), with resistance rates of 74.36% and 71.15% to levofloxacin, respectively. Conclusion: Levofloxacin might be no longer suitable as the first-line choice of clinical experience when performing FURSL in our center.